(Ngeospacializm(B: (Nontologi~eskaq dinamika prostranstwennyh obrazows - (Nzamqtin(B,(Nd(B. (Nn(B.s (2012)
(NoBOSNOWYWAETSQ WWEDENIE NOWOGO DLQ SOCIALXNYH NAUK METODOLOGI^ESKOGO PONQTIQ (B- (NGEOSPACIALIZM(B.s